Glowflex Enterprise : Glow In The Dark Paint / Nur Alisha Mohammad Zarafi ...[et al.] - Mohammad Zarafi, Nur Alisha; Jamaludin, Muhammad Akmal Al Hakimmi; Abdul Halim, Muhammad Danish Asyraaf; Noorazman, Muhammad Afiq Imran; Fadzel, Muhammad farhan; Mohammad, Norhaniza (2014)
As for the business, we are producing a glow in the dark paint for Malaysian. People nowadays want something that simple, easy to use and act effectively but also at reasonable price. We made our paint in convenient packaging form to reduce our cost and market price and also easy to use. Through our long term research and observation, we had planned to set up this business because we can see wider prospect of this sector in the future. Apart from that, we have observed that there are a few competitors that involves in this business. So, we take these opportunities to expand our business because we are qualified with skills.